2019
DOI: 10.1093/gji/ggz364
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of the H–κ stacking technique: implications for global crustal structure

Abstract: SUMMARY H–κ stacking is used routinely to infer crustal thickness and bulk-crustal VP/VS ratio from teleseismic receiver functions. The method assumes that the largest amplitude P-to-S conversions beneath the seismograph station are generated at the Moho. This is reasonable where the crust is simple and the Moho marks a relatively abrupt transition from crust to mantle, but not if the crust–mantle transition is gradational and/or complex intracrustal structure exists. We demonstrate via syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 58 publications
5
67
0
Order By: Relevance
“…6. known as H − κ stacking (Zhu & Kanamori 2000), which may underestimate uncertainties on the retrieved Moho depth, depending on the number of data and the particular approach used (Ogden et al 2019). For some of the estimates used in this study, the authors reported uncertainties as low as 0.3 km, which is below the resolution of the RF data.…”
Section: Datamentioning
confidence: 74%
“…6. known as H − κ stacking (Zhu & Kanamori 2000), which may underestimate uncertainties on the retrieved Moho depth, depending on the number of data and the particular approach used (Ogden et al 2019). For some of the estimates used in this study, the authors reported uncertainties as low as 0.3 km, which is below the resolution of the RF data.…”
Section: Datamentioning
confidence: 74%
“…In a recent paper, Li et al () warn that in the areas where Moho dip is considerable (as is the case here), and/or anisotropy is not negligible, application of traditional H − κ may produce biased results. Likewise, Ogden et al () showed that gradational Moho, as well as complicated crustal structure, will also have adverse effect on the accuracy and confidence of results. The largest uncertainty in Moho depth estimates (>5 km) can be seen in the Central and Southern Dinarides (Figure b) where the combination of limestone cover, thick crust, interface inclination, and deep reflectors all combine to create large lateral variation in the Moho depth estimate.…”
Section: Application Of the Methods And Resultsmentioning
confidence: 99%
“…Grad and Tiira () give an overview of other possible sources of error in H − κ analyses, and Lombardi et al () use synthetic PRFs to warn of overestimation of H by the H − κ method for dipping interfaces. Li et al () performed a thorough analysis of the adverse impact that Moho dip and crustal anisotropy have on estimated H and κ , and Ogden et al () also analyze the considerable influence of gradational Moho, heterogenous crust, and the choice of processing parameters on the final results. In our case, one of the important possible ambiguities stems from multilayered crust.…”
Section: Receiver Function Methodsmentioning
confidence: 99%
“…We believe that the method outlined here will be superior in defining reliable Moho depth estimates in geologically complex regions compared to more commonly applied RF methods such as HK stacking (Zhu & Kanamori, 2000) or inversion for 1-D structure. HK stacking assumes a constant velocity, single-layered crust, which is likely to lead to inaccuracies in areas of more complex crustal structure (Ogden et al, 2019). Inverting RFs for a model of 1-D velocity structure accounts for more variation.…”
Section: 1029/2019tc005986mentioning
confidence: 99%